Magnetically guided recellularization of decellularized stented porcine pericardium-derived aortic valve for TAVI - Ghodsizad, Ali; Bordel, Viktor; Wiedensohler, Hermann; Elbanayosy, Ali; Koerner, Michael Martin; Gonzalez Berjon, Jose M.; Barrios, Roberto; Farag, Mina; Zeriouh, Mohamad; Loebe, Matthias; Noon, George Peter; Koegler, Gesine; et al. (ASAIO journal, 2014)
Application of somatic stem cells for growth, proliferation, and differentiation in a three-dimensional pattern is an important aspect in tissue engineering. Here, we report on our bioreactor, which we applied for magnetically guided recellularization of nitinol-stented valve. Human-derived unrestricted somatic stem cells were cultured in medium in our pulsatile dynamic bioreactor for 4-6 days. Stented valves were prepared by decellularization of porcine pericardium and construction of stented tissue-engineered valves (n = 8). A magnetic field was created around the bioreactor to prevent the loss of cells. In the control group, no magnetic device was used (n = 4). Morphological characterization was assessed by immunohistochemical staining of paraffin sections and electron microscopy. The bioreactor enabled the preservation of physiologic culture conditions with aerobic cell metabolism and physiological pH values. Histological analysis showed homogeneous seeding of the pericardium with progenitor cells in the recellularized samples, whereas no cell seeding could be observed in the nonmagnetic group. Our magnetically guided multifunctional bioreactor allows for an efficient three-dimensional culturing of somatic stem cells on decellularized organ-specific matrix.
Gesehen am 10.09.2020